СПОСТЕРІГАЧ ПАРАМЕТРІВ ПІДВИЩУВАЛЬНИХ DC-DC ПЕРЕТВОРЮВАЧІВ - Ніконенко, Є.О.; Філоненко, М.В. (Інститут електродинаміки Національної академії наук України, 2025)
A new algorithm for self-commissioning procedure of reversible boost-buck DC-DC converters is presented. It does not require prior information about any of their model parameters. It is based on the closed-loop adaptive observer of the DC-link voltage and input current of converter model in average coordinates. Observer provides identification of all parameters namely: resistance and inductance of input inductor, DC-link capacitance and input voltage. Local stability properties are proven for physical operating conditions based on second Lyapunov method. Due to the simple structure of the observer, it can be used as part of adaptive voltage control systems for buck- boost DC-DC converters. For such an adaptive system, an additional estimating law is designed for the coordinate disturbance, the load current. Simulation results show fast convergence of the estimation errors of parameters and the load current. Ref. 17, fig. 5.